Mollusca, Bivalvia, Corbiculidae, Corbicula fluminea (Müller, 1774): first record for the Caatinga biome, northeastern Brazil - Santana, Daniel Oliveira (2013)
Corbicula fluminea is native mollusk from China. In Brazil, this species was first recorded in Rio Grande do Sul state in the late 70’s, being also recorded in the Amazonia basin between 1997 and 1998. The present note reports the occurrence of C. fluminea for the first time in the Caatinga biome and extends considerably the geographical distribution of this invading species in Brazil and consequently in South America.